Orofacial Granulomatosis Treated with Systemic Steroid: A Case Report - Jha, Prasanna Kumar (Nepal Medical College Journal, 2021)
Orofacial granulomatosis refers to conditions restricted to oral region mainly characterized by chronic swelling of orofacial tissues with histological evidence of non-caseating granuloma. It may be idiopathic where there is absence of identifiable granulomatous disease or may present as a component of localized or generalized Crohn’s disease, tuberculosis and sarcoidosis. The clinical features are facial or lip swelling, angular cheilitis, oral ulcerations, vertical fissures of lips, gingival enlargement, mucosal tags and sometimes lymph node enlargement. A middle-aged female presented to our outpatient department with diffuse chronic swelling of lips which after treatment with systemic steroid showed visible improvement during follow up.